Acetylation unit at Hercules Parlin plant - Hercules Incorporated (1961)
General view of an acetylation unit used in the production of Penton, a chlorinated polyether used as an ingredient in protective coatings for structural steel and other metals, papers, cardboard, and plastics, at the Hercules Powder Company plant in Parlin, New Jersey. The employee visible in the photograph is unidentified. Per notations accompanying the photograph, the acetylation unit included a Pentaerythritol feed system, a feed tank, and a dissolver containing acetic acid and catalysts. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Employees; Chemical industry; Hercules Incorporated; Corporations; Machinery